Critics as "bricoleurs": some remarks - Catelli, Nora (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
What is the relationship between Theory and Comparative and World Literature; how is that link thought? And, in my case, what are the objects on which we work, taking into account this difficult crossing today?I pick up these questions for this dialogue with Túa Blesa, which gives them a renewed and, perhaps, lighter meaning.
Keywords: Theory; Comparative Literature; World Literature